PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 KOTO BARU KABUPATEN DHARMASRAYA TAHUN PELAJARAN 2013/2014 - Raflesia, Rani; K, Delsi; Cesaria, Anna (Pendidikan Matematika, 2013)
The research is motivated by Â studentsâ understanding of mathematical concepts that still low and the material that students have was lost from their mind. This reserach is to determine wether studentsâ understanding of Â Â mathematical conceptsÂ  by using a strategy Hollywood square Review better than studentsâ understanding of mathematical concepts by using conventional strategy at VIII Grade of SMP N 1 Koto Baru. Type of this research was experiment. Population in this research was students at VIII grade of SMP N 1 Koto Baru, and sample of this research was students class VIIIA as experimental class and VIIIc as control class. Post-test was as instrumentation in this research, with realibility 0,88. From the data analysis get mean score from studentsâ achievement in experimental class was 66,22 that highÂ  rather than in control class that was 35,68. data analysis was done by using hypothesis testing. Tcalculated= 4,15 and ttable= 1,65. so, we can conclude that studentsâ understanding of Â mathematical concepts that used Hollywood Square Review better that conventional strategyÂ  at VIII Grade of SMP N 1 Koto Baru